Leaching of heavy metals from cementitious composites made of new ternary cements - Kuterasińska-Warwas Justyna; Król Anna (E3S Web of Conferences, 2017)
The paper presents a comparison of research methods concerning the leaching of harmful substances (selected heavy metal cations ie. Pb, Cu, Zn and Cr) and their degree of immobilization in cement matrices. The new types of ternary cements were used in the study, where a large proportion of cement clinker was replaced by other non-clinker components - industrial wastes, ie. siliceous fly ash from power industry and granulated blast furnace slag from the iron and steel industry. In studied cementitious binders also ground limestone was used, which is a widely available raw material. The aim of research is determining the suitability of new cements for neutralizing harmful substances in the obtained matrices. The application of two research methods in accordance with EN 12457-4 and NEN 7275 intends to reflection of changing environmental conditions whom composite materials may actually undergo during their exploitation or storing on landfills. The results show that cements with high addition of non-clinker components are suitable for stabilization of toxic substances and the obtained cement matrices retain a high degree of immobilization of heavy metals at the level of 99%.